Analysis of Factors Influence Employee Job Satisfaction Study at PT. Surya Jaya Teknik - Nurdiana, Fitria; Susiati, Asriani (Cv. Syntax Corporation Indonesia, 2025)
Increasing employee job satisfaction is an important factor in supporting organizational performance and success. PT Surya Jaya Teknik as a manufacturing company in the automotive sector faces challenges related to employee job dissatisfaction which is influenced by suboptimal working environment conditions, motivation, and compensation. This study aims to analyze the factors that influence employee job satisfaction case study at PT Surya Jaya Teknik. This research uses SPSS version 25. The data analysis method used is quantitative by involving 98 respondents who are employees at PT Surya Jaya Teknik. Data analysis was performed using multiple linear regression. The results of the study partially show that work environment, motivation, and compensation have a positive and significant effect on job satisfaction. Simultaneously, work environment, motivation, and compensation together have a significant effect on work effectiveness. This identifies that factors that affect employee job satisfaction such as work environment, motivation, and compensation have an effect in increasing job satisfaction in employees. The practical implication of this research is that companies need to pay attention to and manage these three factors as a strategy to improve performance and maintain the quality of human resources.